Parsing adverbial complex sentences in ASD-STE100 within ARTEMIS - Martín Díaz, María Auxiliadora (Complutense Journal of English Studies, 2019)
One of the main objectives of Natural Language Processing is the simulation of natural language understanding. Within the applications designed for this purpose today, ARTEMIS follows the paradigm of unification grammars (Sag, I., Wasow, T. & Bender, E. 2003), and unlike other trending computational resources, it is theoretically grounded in linguistic models like RRG (Van Valin & LaPolla 1997 and Van Valin 2005), whose linking algorithm lies at the basis of the parsing process of our interlingua-based system. A fundamental component of ARTEMIS is the Grammar Development Environment (GDE), where feature-based production rules (syntactic, constructional and lexical) are stored and ready to allow the generation of the enhanced layered structure of the clause of natural language expressions (Periñán-Pascual 2013: 222). Syntactic rules for phrasal constituents and simple sentences have already been described (Cortés-Rodríguez 2016; Cortés-Rodríguez & Mairal-Usón 2016; Díaz-Galán & Fumero-Pérez 2015; Fumero-Pérez & Díaz-Galán 2017; Martín-Díaz 2017 and Martín-Díaz 2018), but it now turns to focus on complex sentences, and, to be more precise, on adverbial subordination. Bearing in mind the validation of these syntactic rules and the common problems that may arise in such parsing applications, our research will concentrate on the analysis of these structures as found in a Controlled Natural Language: ASD-STE100.